2016
DOI: 10.12816/0026145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Parasitological Studies on Pulmonary and Hepatic Hydatid Cysts in Hospitalized Children and Adults

Abstract: A cross sectional study compared the clinical features of the pulmonary and hepatic hydatid cysts in children and adults and evaluated IHAT and ELISA techniques in diagnosis. The results showed that the patients ages were 5-14 years (10.6±3.7) in children and 16-75 years (32.2±14) in adults, patients 34 (75.5%) had liver cysts, 25 (55.5%) had pulmonary cysts and 7 (15.5%) had both liver and lung cysts. In hepatic hydatidosis, 7/34 (20.5%) cases were asymptomatic while others showed variable clinical manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The hydatid cyst affects children and adults and both are susceptible to infection [16]. Our study showed that three children were affected (1.9%), this percentage is underestimated due to under-reporting of cases.…”
Section: Ce In Childrenmentioning
confidence: 54%
See 1 more Smart Citation
“…The hydatid cyst affects children and adults and both are susceptible to infection [16]. Our study showed that three children were affected (1.9%), this percentage is underestimated due to under-reporting of cases.…”
Section: Ce In Childrenmentioning
confidence: 54%
“…A study in Egypt [16] between 2013 and 2015 upon 45 patients showed that the hepatic hydatidosis prevalence increased in the age group > 40 years.…”
Section: Distribution Of Cases By Age and Gendermentioning
confidence: 99%
“…This agreed with Salama et al (2014) in Egypt, Chalechale et al (2016) in Iran, Also Abdulhameed et al (2018) in Iraq particularly the right upper quadrant causing abdomen pain. El- Ghareeb et al (2016) reported asymptomatic hepatic hydatidosis patients (20.5%) as well as pulmonary ones (21.7%), but El-Sayed et al (2020) reported symptomatic lung patients presented with chronic cough (sometimes with accompanied with hemoptysis or evacuation of cyst material), chest pain, pleuritis or dyspnea, with more than one sign and symptoms in same patient mainly with lung infection. The clinical variations could due to variable sizes and sites of hydatid cysts exerting different mass effects on surrounding organs and complications (WHO, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic hydatidosis cases were the commonest finding by 22.03% in the study of [26] and all variations in clinical data were due to variable sizes and sites of hydatid cysts exerting different mass effects on surrounding organs and complications were related to cysts rupture [32]. Other studies like [33] showed that the patient's reaction to hydatid infection ranged from tolerance for a long period without any symptoms to sudden, intense acute symptoms.…”
Section: Discussionmentioning
confidence: 99%